The Relationship Between The Level of Knowledge of Nurses and Response Time in The Emergency Installation at Porsea Regional General Hospital Toba Regency - Melva Epy Mardiana Manurung; Jenti Sitorus; Ayu Hutahaean (Institute Of Computer Science (IOCS), 2022)
Emergency Room is the main access to get treatment at the hospital, has a very important role in treating patients with various levels of emergency. Response Time is the speed in handling patients, calculated from the time the patient arrives until the treatment is carried out. In carrying out special health services in the emergency department, one of the indicators that must be achieved is handling the right response time to achieve the expected results. The standard response for emergency patients must be served no later than 5 (five) minutes after arriving at the emergency department. This research method is a cross sectional study to determine the relationship between nurses' knowledge and response time in the Emergency Installation of the Porsea Regional Hospital, Toba Regency, which was carried out in February 2022 on 17 emergency room nurses at Porsea Regional General Hospital using a total sampling technique. The results of the study found that there was a relationship between Nurse Knowledge Levels and Response Time in the Emergency Room using the Chi-Square test, p value = 0.007, p value < (0.05). So it can be concluded Ha, which means that there is a relationship between the level of knowledge of nurses and response time in the ER at the Porsea Regional Hospital in 2022. It is expected that nurses will continue to improve their skills/insights and knowledge by optimizing in providing services in the form of comprehensive nursing actions.